Effectiveness and Contribution of Regional Taxes and Retribution Towards Regional Original Income of Tanah Laut Regency - Rininda, Bella Puspita; Ismaiyah, Ismaiyah (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This research was conducted to determine the effectiveness of regional tax collection and regional retribution, as well as their contribution to the Regional Original Revenue (PAD) in Tanah Laut Regency. Additionally, this study also reveals the growth rate of local taxes and regional levies. The data used are secondary data in the form of realization reports of local tax and regional levy revenues from 2015 to 2019, which are then projected for the year 2020. Based on the results of this research, it can be observed that over the past five years, the realization of local taxes and regional levies has consistently exceeded the targets, indicating a high level of effectiveness. However, their contribution to PAD is still considered insufficient. When examining the development of local tax revenues, the growth rate has not reached its maximum potential. The same applies to regional levy revenues. Therefore, in the coming years, the local government needs to make efforts to enhance local tax and regional levy revenues while adhering to existing regulations.